Optimalisasi Kesehatan Organ Reproduksi Wanita Melalui Senam “SI-EPIN” - Naomi Parmila Hesti Savitri; Sri Wahyuni (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT Reproductive health is a crucial aspect of a woman's quality of life. However, lack of physical activity, high stress levels, and an unbalanced diet often disrupt blood circulation and negatively impact uterine health. An effective non-pharmacological approach is the